Hubungan Kepatuhan Penggunaan APD Dan Lama Kerja Dengan Gangguan Fungsi Paru Pada Karyawan PT.XYZ Pasuruan Bagian Logistik - Widi, Wahyu Purnama; Suhartini, Titik (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Occupational lung disease is a disease that occurs due to inhalation of dangerous particles, mist, vapor or gas while a person is working. Ammonia, which is also a chemical substance, has dangerous effects on humans, one of which is inhalation of ammonia, which can cause acute lung injury and pulmonary edema and even death. Impaired lung function is not only caused by high dust levels, but several factors characteristic of the worker himself can also influence the condition of the lungs, such as age, smoking habits, history of lung disease, compliance with the use of of personal protective equipment (PPE), nutritional status, sports activity and length of work. Methods: This study aims to analyze the correlation between compliance with PPE use and length of work with lung function disorders in PT employees. XYZ Pasuruan logistics division. This study used a correlational analytic design retrospective cohort approach using observation sheets and MCU spirometry results and analyzed using SPSS software. Research location was PT. XYZ Pasuruan has 2 locations, namely the chemical logistics section with 12 employees and the ammonia terminal section with 12 employees. Results: The results of the analysis using a statistical regression test of compliance with PPE use and length of work with impaired lung function obtained a P value of 0.000, so it was concluded that there was a significant correlation between compliance with PPE use and length of work with impaired lung function. The results of other research show that there are variations in working hours, use of PPE and vital lung capacity among workers. From the statistical tests, the p value obtained for the correlation between working years and impaired vital lung capacity was 0.001 and the p value for the correlation between PPE use and impaired lung function was 0.000. Conclusion: This is in line with research conducted by PT. XYZ that there is a correlation between compliance with PPE use and length of work with significant lung function disorders.